Correlation of pregnancy classes on knowledge and attitudes about childbirth preparation at Puskesmas Terminal Banjarmasin - Karmila, Sari; Palimbo, Adriana; Lestari, Yayuk Puji; Dona, Sismeri; Jannah, Raudhatul (Health Sciences International Journal, 2026)
Background: Maternal mortality remains a critical public health concern in Indonesia. Pregnancy classes are a strategic intervention to enhance maternal knowledge and attitudes towards childbirth preparation, yet participation rates and their impact require further investigation, particularly at the primary healthcare level. Objective: This study aimed to analyze the correlation between participation in pregnancy classes and the level of knowledge and attitudes regarding childbirth preparation among pregnant women at the Terminal Banjarmasin Community Health Centre. Method: An analytical cross-sectional study with a correlational design was conducted from May to July 2025. A total population sample of 34 pregnant women registered in the classes was enrolled. Data were collected using an attendance sheet and a validated questionnaire on knowledge (20 Guttman-scale items) and attitudes (18 Likert-scale items). Data analysis employed Fisher's Exact Test to determine the relationship between attendance (categorized as optimal [≥4 sessions] or suboptimal [<4 sessions]) and knowledge/attitude levels, with a significance level of α=0.05. Results: The majority of participants (70.6%) had suboptimal attendance. Half (50%) had insufficient knowledge and 55.9% held a negative attitude. A statistically significant correlation was found between optimal class attendance and higher knowledge levels (p < 0.001) and more positive attitudes (p < 0.001). All participants with optimal attendance had sufficient/good knowledge and positive attitudes. Conclusion: Optimal participation in pregnancy classes is significantly correlated with improved knowledge and positive attitudes towards childbirth preparation. Program strategies should shift focus from mere enrolment to ensuring consistent attendance and completion to maximize educational outcomes and contribute to safer childbirth practices.